STUDIES OF MORPHOLOGICAL CHARACTERS FOR REPRESENTATIVES OF POPULUS GENUS - Torosova, L. A.; Vysotska, N. Yu.; Los, S. A.; Orlovska, T. V.; Zolotyh, I. V. (Forestry and Forest Melioration, 2018)
Introduction Researchers engaged in poplar breeding and growing throughout the twentieth century. Under the guidance of N. V. Starova, in Ukraine the late fifties, interspecific hybridization of poplar was conducted in massive scale. Now the studies of the rate of growth, resistance and morphological characteristics of different species, hybrids and varieties of poplars are proceeding. The aim of this work was to improve the methods of studying of variety of poplar leaves morphological characters and study morphological and morphometric characteristics of certain species, hybrids, varieties and clones of poplar for forming them detailed description. Materials and Methods According to the development of methodologies for evaluating morphological diversity of leaves, length and width of leaf blade, leaf petiole length were measured. The shape of the leaves, its top, base and edge, availability pubescence were evaluated. For winter shoots, meritallus length, size of buds and color of the bark were determined. Results Detailed morphological characteristics and morphometric characteristics of leaves, shoots and buds for 19 species, hybrids, varieties and clones of poplars were done. There were investigated 19 species, varieties and hybrids of poplars; 8 varieties belong to the Ukrainian breeding (Drughba, Lvivska, Lada, Karolinska, Nocturne, Novoberlinska, Rohanska, Strilopodibna); 4 – Russian breeding (Versiya, Veryla, Ivanteyivska, Rosijska); 2 – Italian (Addita, Tronko); 1 – German breeding (Ваheliyeri). Their characteristics were summarized. Conclusions The studying technique of variety of poplar leaves morphological characteristics was improved using scoring individual characteristics. The full description of the variety should include the length and width of leaf blade, coefficient of leaf blade form, the length of the leaf stem, shape of leaf blade, its apex, base and edge; presence of hairs on the back of the leaf blade and the veins, length of internodes shoots and buds dimensions. Compiled detailed morphological characteristics and morphometric characteristics of leaves, shoots and buds for 19 species, hybrids, varieties and clones of poplar can be used for identification.